A Hungarian Orphan’s Rare Courtly Career in the Spanish Monarchy: Martin Somogyi’s Service at the Spanish Habsburg Court in Brussels, 1594–1631 - Monostori, Tibor (Historical Studies on Central Europe, 2024)
Martin Somogyi, a Hungarian orphan and nobleman spent nearly forty years in the service of the Habsburg dynasty, most of that time in Brussels, the capital of the Spanish Netherlands. Via the Dietrichstein and Cardona families, from his childhood he received extraordinary patronage and was a close confidant of several family members, while providing constant courtly services to them and to Albert and Isabella, archdukes and governors of the Spanish Netherlands. Ha became baron and estate owner in both Flanders and Moravia, and from Brussels he repeatedly went on diplomatic missions to Central Europe. Having spent thirty years as vice-captain of the governors’ personal guards, his patrons including Archduke Albert requested a Spanish Order of Cavalry for him, but with no effect. By the 1620s, Somogyi’s career reached its peak and his dissatisfaction was growing. Therefore, he requested from Dietrichstein his return to Central Europe, but again with no success. He died without male offspring, and his descendants still live in Belgium. Somogyi is also known for having sent to Central Europe one of the first issues of the second part of Miguel de Cervantes’ Don Quijote de la Mancha.